The Role of the United States in the Formation of BRICS - Rodrigo Ruiz (Journal of BRICS Studies)
This article critically examines the formation of the BRICS alliance, comprising Brazil, Russia, India, China, and South Africa, with a specific focus on the pivotal role played by the United States in shaping this strategic partnership. It explores the extent of US influence and the accompanying responsibilities it assumes within the alliance. The article highlights the proactive efforts of Brazil, Russia, and China to expand their global influence while concurrently aiming to reduce US interference. Brazil, in particular, seeks partnerships with Russia and China as a means to attain autonomy and foster development. Simultaneously, Russia and China strive to challenge US global dominance and solidify their own spheres of influence. The article concludes by emphasising the importance of critically evaluating Europe's military support to Ukraine, suggesting that such support may primarily serve US interests. Additionally, it underscores Europe's potential to promote peace and stability by pursuing independent and principled foreign policies.